2022
DOI: 10.1109/tbme.2021.3088232
|View full text |Cite
|
Sign up to set email alerts
|

In-Vitro Study of Speed and Alignment Angle in Cochlear Implant Electrode Array Insertions

Abstract: The insertion of the electrode array is a critical step in cochlear implantation. Herein we comprehensively investigate the impact of the alignment angle and feed-forward speed on deep insertions in artificial scala tympani models with accurate macro-anatomy and controlled frictional properties. Methods: Motorized insertions (n=1033) were performed in six scala tympani models with varying speeds and alignment angles. We evaluated reaction forces and micrographs of the insertion process and developed a mathemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
44
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 58 publications
5
44
1
Order By: Relevance
“…Our findings were reflected in a study recently published by Aebischer et al (19). The authors reported higher insertion forces with higher insertion speed across six different ST models (19). This was reflected in our study as well.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our findings were reflected in a study recently published by Aebischer et al (19). The authors reported higher insertion forces with higher insertion speed across six different ST models (19). This was reflected in our study as well.…”
Section: Discussionsupporting
confidence: 89%
“…Earlier reports by Kontorinis et al and Landry et al indicated that higher insertion speed was associated with higher insertion forces ( 17 , 18 ). Our findings were reflected in a study recently published by Aebischer et al ( 19 ). The authors reported higher insertion forces with higher insertion speed across six different ST models ( 19 ).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Consequently, most losses of residual hearing occurred intraoperatively or in the early postoperative phase. Reasons can be a traumatic electrode insertion (9,23,24) or an inflammatory response with resulting scar tissue formation (12)(13)(14). In addition, the presence of the electrode array can influence the mechanical properties of the cochlea and, thus, residual hearing thresholds (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Intra-cochlear electrode insertion is considered one of the crucial steps of a successful CI surgery. In particular, studies have suggested that slow steady insertion (achieved more easily with robotic insertion) can reduce pressure changes within the cochlea ( 5 , 6 ), reduce insertion forces ( 7 ), and increase the likelihood of an in-axis insertion into ST and improve hearing outcomes ( 8 ). Robotic-assisted cochlear implant surgery (RACIS) aims to optimize this insertion process by (1) computer control of insertion speed and by applying insertion forces more steadily and smoothly, (2) defining the angle with which the electrode is inserted into the ST, and (3) improving the estimated insertion depth to minimize trauma and provide better hearing outcomes.…”
Section: Introductionmentioning
confidence: 99%